2015
DOI: 10.1021/acs.jpclett.5b01692
|View full text |Cite
|
Sign up to set email alerts
|

Origin of Unusual Excitonic Absorption and Emission from Colloidal Ag2S Nanocrystals: Ultrafast Photophysics and Solar Cell

Abstract: Colloidal Ag2S nanocrystals (NCs) typically do not exhibit sharp excitonic absorption and emission. We first elucidate the reason behind this problem by preparing Ag2S NCs from nearly monodisperse CdS NCs employing cation exchange reaction. It was found that the defect-related midgap transitions overlap with excitonic transition, blurring the absorption spectrum. On the basis of this observation, we prepared nearly defect-free Ag2S NCs using molecular precursors. These defect-free Ag2S NCs exhibit sharp excito… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
31
0
5

Year Published

2016
2016
2022
2022

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 75 publications
(39 citation statements)
references
References 40 publications
3
31
0
5
Order By: Relevance
“…42 For a 4.5 nm Ag 2 S (3-6.5 nm) with emission at 850 nm, biexponential decay with 1 and 11 ns was reported and the later was attributed to the excitonic recombination. 42 In another study, 1.5 nm Ag 2 S with emission maxima at 813 nm was reported to have an average lifetime of 57 ns, which was attributed to the radiative decay related to surface inhomogeneities. 3 Zhang et al reported increasing lifetimes for Ag 2 S-dodecanethiol with increasing crystal size.…”
Section: Characterization Of Pei/cys Coated Ag 2 S Qdsmentioning
confidence: 97%
“…42 For a 4.5 nm Ag 2 S (3-6.5 nm) with emission at 850 nm, biexponential decay with 1 and 11 ns was reported and the later was attributed to the excitonic recombination. 42 In another study, 1.5 nm Ag 2 S with emission maxima at 813 nm was reported to have an average lifetime of 57 ns, which was attributed to the radiative decay related to surface inhomogeneities. 3 Zhang et al reported increasing lifetimes for Ag 2 S-dodecanethiol with increasing crystal size.…”
Section: Characterization Of Pei/cys Coated Ag 2 S Qdsmentioning
confidence: 97%
“…Monoclinic α‐Ag 2 S is a promising candidate in wide application such as quantum dots sensitized solar cell (QDSSCs), photo catalysis and bioimaging due to its narrow band gap (0.9‐1.1 eV), relatively large optical absorption coefficient and its environment friendly nature. Till date, different methods have been developed for the synthesis of Ag 2 S QDs and thus obtained QDs have been used in biomedical applications such as in vitro,, and in vivo,, imaging.…”
Section: Introductionmentioning
confidence: 99%
“…The stability of Ag 2 S quantum dots produced by successive ionic layer adsorption and reaction (SILAR) as well as their ability to inject electrons into an n-type semi-conductor, such as TiO 2 , have been investigated [20]. Above 1% solar to electricity power conversion efficiency (PCE) using a device structure similar to the dye-sensitized solar cells has been achieved [21][22][23][24]. However, there have been no reports on solar cells based on solid CQD layers with Ag 2 S, similar to the solid CQD layers used in the most efficient PbS CQD solar cells discussed above.…”
Section: Introductionmentioning
confidence: 99%